Sustainable Healthcare: Medical Waste Management, Energy Resource Efficiency, and Environmentally Preferable Behaviors - Raikhola, Pushkar Singh (NPRC Journal of Multidisciplinary Research, 2025)
This study explores the perceptions of respondents toward environmental sustainability in the healthcare sector, focusing on three key areas: Medical Waste Management (MWM), Energy and Resource Efficiency (ERE), and Environmentally Preferable Behaviors (EPB). A structured questionnaire was administered to 209 participants, and descriptive statistics along with one-sample t-tests were employed to analyze the data. The results revealed high levels of agreement across all three dimensions, with mean scores of 4.10 for MWM, 4.12 for ERE, and 4.19 for EPB on a 5-point Likert scale. One-sample t-test results confirmed the statistical significance of these findings (p < .001), indicating strong environmental awareness and preference for sustainable healthcare practices among respondents. Particularly, participants emphasized the need for safe disposal of medical waste, adoption of energy-efficient systems, and training of healthcare professionals in sustainability. The study concludes that there is a strong public inclination toward integrating green practices within healthcare institutions.